Hypno Public Speaking Training as a Strategy to Strengthen the Communication Capacity of Muhammadiyah Student Association Cadres in the Society 5.0 Era - Fais Wahidatul Arifatin (Universitas Muhammadiyah Sidenreng Rappang, 2026)
The transformation of society in the Society 5.0 era requires young generations to possess adaptive, persuasive, and leadership-oriented communication competencies. However, cadres of Ikatan Pelajar Muhammadiyah (IPM) still encounter various obstacles in public communication, including low self-confidence, anxiety in public speaking, and limited mastery of effective public speaking techniques. This community service program aimed to enhance the communication capacity of IPM cadres through hypno public speaking training as an innovative approach integrating public communication techniques with psychological reinforcement. The program employed a participatory action research approach consisting of needs analysis, preparation, training implementation, mentoring, and evaluation stages. The activity was conducted at the branch level of IPM Solokuro involving 67 participants. Training materials included the fundamentals of public speaking, digital da’wah, relaxation techniques, audience management, and hypno public speaking practices. The findings indicated improvements in participants’ communication abilities as reflected in the pre-test and post-test results, increased self-confidence, better vocal intonation control, improved stage mastery, and greater courage in expressing ideas publicly. In addition, the satisfaction evaluation demonstrated positive participant responses toward the implementation of the training. Therefore, hypno public speaking training can be considered an effective model for strengthening the communication capacity of student organization cadres in the Society 5.0 era.